The legacy of the dot-com bubble: Financial lessons on speculation and fundamentals - Khan, Muhammad Arsalan; Kurnianto, Sigit; Malik, Atiqa (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2024)
The dot-com bubble burst in the early 2000s marked a pivotal moment in financial market history, revealing the dominance of speculative investment behavior over traditional financial fundamentals. This study revisits the dot-com bubble era, focusing on the relationship between key financial metrics (total sales, total assets, net income, total debt, and share price) during a period of intense market speculation. By analyzing these fundamental indicators, the study provides insights that are still relevant modern speculative trends driven by technologies like AI, blockchain, and the metaverse.  Examining 30 U.S. companies during the dot-com bubble (1995–2001) and its aftermath (2001–2011) using multiple regression analysis and the Wilcoxon test, we find that total sales, net income, and total debt positively influenced share prices, while total assets had a negative impact. These findings suggest that investor optimism prioritizes growth, profitability, and aggressive financing during speculative periods over traditional indicators like asset size, which are often associated with slower-moving business models. The Wilcoxon test further reveals significant differences in median stock prices between the bubble and post-bubble periods, underscoring the valuation shifts driven by speculative and fundamental factors. By examining historical market behaviors, this study highlights the lasting importance of aligning speculative enthusiasm with financial fundamentals, providing valuable lessons for understanding speculative markets.